Chapter Biografie, spazi, contesti: educare alla Storia - Mazzoni, Matteo (Public History of Education. Teorie, esperienze, strumenti, 2022)
In this years, historical witnesses of the Resistenza movement are dissolving. In this context where historical knowledge is facing with a growing crisis, how can we stimulate young generation's interest twoards the Resistance movement? The paper tries to answer to this request. Particularly, we are going to propose two hypothesis for didactical work. Firslty, deepening studies about the men and the women who faced with unexpectable choices; secondly, the analysis of places known by students but not appreciated in their historical meaning. In this way, we can approach people to history.